Characterization of CD4(+) CTLs ex vivo. - Appay, V; Zaunders, J; Papagno, L; Sutton, J; Jaramillo, A; Waters, A; Easterbrook, P; Grey, P; Smith, D; Mcmichael, A; Cooper, D; Rowland-Jones, S; et al. (2002)
The cytotoxic potential of CD8(+) T cells and NK cells plays a crucial role in the immune response to pathogens. Although in vitro studies have reported that CD4(+) T cells are also able to mediate perforin-mediated killing, the in vivo existence and relevance of cytotoxic CD4(+) T cells have been the subject of debate. Here we show that a population of CD4(+) perforin(+) T cells is present in the circulation at low numbers in healthy donors and is markedly expanded in donors with chronic viral infections, in particular HIV infection, at all stages of the disease, including early primary infection. Ex vivo analysis shows that these cells have cytotoxic potential mediated through the release of perforin. In comparison with more classical CD4(+) T cells, this subset displays a distinct surface phenotype and functional profile most consistent with end-stage differentiated T cells and include Ag experienced CD4(+) T cells. The existence of CD4(+) cytotoxic T cells in vivo at relatively high levels in chronic viral infection suggests a role in the immune response.